Bullying in secondary schools what it looks like and how to manage it - Sullivan, Keith; Cleary, Mark, 1953-; Sullivan, Ginny; Sage eBooks (London : Paul Chapman, 2004)
Examining the nature of the secondary school and the typology of the adolescent, this work is a practical guide to dealing with bullying in secondary schools.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Bullying in schools; Bullying in schools -- Prevention; High school environment; Electronic books